Time Related Work Life Balance Practices Influencing Employee Job Satisfaction in Machakos County Commercial Banks, Kenya - Muema, Felisters N.; Nzioki, Susan; Kinyili, Jacinta (International Journal of Economics, Commerce and Management, 2018)
Work-Life balance among employees has emerged as an issue of concern to both employees and employers. There has been growing attention to employees’ inability to dedicate proper attention and time to one’s non-work activities and obligations which often leads to dissatisfaction with their job. The main objective of this study was to examine the influence of Work -Life Balance practices relating to time on employee job satisfaction in Commercial Banks in Machakos County, Kenya. A descriptive survey research design was used to gather both quantitative and qualitative data from employees in the sixteen banks with a target population of three hundred and eighty (380). Stratified random sampling technique was used to select a sample size of one hundred and ninety-one (191) respondents. The researcher used structured questionnaires to collect data. Questionnaires were administered to the selected employees of all cadre in the commercial banks. The Statistical Package for Social Science (SPSS) was used to analyse data collected. Inferential statistics, that is, regression and the Pearson Correlation Coefficient were used to analyse the relationships between the study variables. The study established that Work Life Balance practices relating to time positively influenced employee job satisfaction. This, therefore, recommends that commercial banks improve on flexible working arrangements in order to boost employee job satisfaction.
Keywords: Commercial banks; Flexible Working Arrangements; Job satisfaction; Work Life Balance; Work life balance practices